Independent Living for the Elderly at Home: What is Required? - Walker, Barbara Prime (1986)
Home care is vital to healthy aging, since living autonomously in the community is the primary interest of the elderly. Breaking the cycle which locks many frail and disabled individuals into a position of dependency requires shared input from a variety of resources in society. Success depends on an accurate assessment of functional ability, knowledge of community support services, and the willingness of health professionals to work co-operatively with others to provide a balance of assistance which is realistic for the local community.